Efficacy of doublesynch, estradoublesynch and progesterone based protocols for improving fertility in anoestrus Surti buffaloes - Dhami, Arjun J; Patel, Arpit J; Patel, J A; Prajapati, A R; Sarvaiya, N P (Indian Journal of Dairy Science, 2017)
This study was undertaken to find out the estrus induction and fertility response and monitor the peripheral plasma progesterone profile in 55 postpartum anoestrus buffaloes (>90 days) treated with Doublesynch, Estradoublesynch, PRID (Triu-B) and PRID + PMSG protocols (n=11 each), keeping a group of untreated anoestrus control (n=11). The induction of behavioural estrus in four protocols was 81.81, 90.90, 100.00 and 90.90 % within mean intervals of 64.77±2.19, 62.50±1.39, 61.45±1.34 and 64.00±1.25 hrs from PGF2α injection, respectively. The conception rates obtained at induced estrus with FTAI in above four protocols were 27.27, 27.27, 18.18 and 45.45 per cent, and overall of three cycles’ as 63.63, 54.54, 63.63 and 81.81 per cent, respectively. In untreated control group, only two buffaloes (20.00%) evinced estrus and conceived over a period of 90 days follow up. The mean plasma progesterone (P4, ng/ml) concentrations were low towards basal values (